Personalizing the Way of Teaching LSP - Tatiana S. Makarova; Eugenia E. Matveeva; Maria A. Molchanova; Elena A. Morozova; Natalia V. Burenina (National Research Mordova State University, 2023)
Introduction. The problem of effective teaching language for special purposes (LSP) to the students of non-linguistic professions has been discussed for a long time and in full details by academicians both in Russia and foreign countries. As the result of multiple and thorough surveys general problems of the given situation have been revealed, the way out being defined as special training/retraining of LSP teachers. But in language education publications it is hardly possible to find the description of the program aiming at the training of the above mentioned teachers. The aim of the article is to present effective approaches to teaching LSP and offer the developed master program "Methods of teaching LSP" as a means to solve the problems mentioned above. Materials and Methods. The research methods used are a combination of analytical review of studies by Russian and foreign researchers and interpretation of the results obtained by interviewing university teachers specializing in teaching foreign languages to students completing Bachelorʼs or Masterʼs degree programs. The survey was conducted to assess the level of readiness of professional educators to design the structure and content of programs for teaching LSP, and actually conduct classes within the specified language-teaching area, 81 teachers being responders. Results. As a result of the undertaken review of theoretical works and analysis of the conducted survey a master program "Methods of teaching LSP" was designed for training graduates who will then teach English or Russian as a foreign language at industry-specific higher schools. The developed program focuses on instructing future LSP educators to work out a personalized educational route adjusted to the level of foreign language skills of a student and their prospective professional activities. Discussion and Conclusion. The master program developed by the authors as well as the content of the subjects suggested as its integral part are expected to become a productive way of training LSP educators who are supposed to acquire a number of special skills and competences described in the article. Distant learning and e-learning technologies are also engaged in the program to facilitate learners' more efficient independent activities. The master program is seen as one of the means of modernizing LSP teachers' professional training which meets the long-term needs of the Russian education system.